Cell-Specific Dual Role of Caveolin-1 in Pulmonary Hypertension - Rajamma Mathew (Pulmonary Medicine)
A wide variety of cardiopulmonary and systemic diseases are known to lead to pulmonary hypertension (PH). A number of signaling pathways have been implicated in PH; however, the precise mechanism/s leading to PH is not yet clearly understood. Caveolin-1, a membrane scaffolding protein found in a number of cells including endothelial and smooth muscle cells, has been implicated in PH. Loss of endothelial caveolin-1 is reported in clinical and experimental forms of PH. Caveolin-1, also known as a tumor-suppressor factor, interacts with a number of transducing molecules that reside in or are recruited to caveolae, and it inhibits cell proliferative pathways. Not surprisingly, the rescue of endothelial caveolin-1 has been found not only to inhibit the activation of proliferative pathways but also to attenuate PH. Recently, it has emerged that during the progression of PH, enhanced expression of caveolin-1 occurs in smooth muscle cells, where it facilitates cell proliferation, thus contributing to worsening of the disease. This paper summarizes the cell-specific dual role of caveolin-1 in PH.